THE EFFECTS OF THE ECONOMICS, SOCIAL, ENVIRONMENT, LAY-OUT OF THE CITY AND PUBLIC ORDER UPON THE PERFORMANCE OF THE PUBLIC CULINARY STALLS / PKL - Erni Yuningsih; Dwi Gemina; Sri Harini (The Management Journal of Binaniaga, 2016)
The public culinary stalls (PKL) are an informal economic sector that have been evolving in big cities especially in Bogor. The Government is obliged to manage and arrange the public culinary stalls in order not to disturb the society, lay-out of the city, and public order. Public Cullinary Stalls have been increasing the society economics and supporting the government relating to jobs opportunities. This research aims to discover: 1) the profile of public culinary stalls 2) a simultaneous effects of the aspects of economics, social, environment, lay-out of the city and public order aspects upon PKL performances, and 3) a partial effects of the aspects of economics, social, environment, lay-out of the city and public order upon PKL performance The research has been applying a qualitative and quantitative approach. Data collection has been obtained through the questionnaires distribution, the observation and depth interview. The research has determined that the economics, society, environment, lay-out of the city an, public order factors have been affecting simultaneously and partially the performance of PKL.Key-words : Economics, Social, Environment, Lay-out, public order and Performance of PKL.